Deploying QoS for Cisco IP and Next Generation Networks - Joseph, Vinod (Elsevier, 2011)
Deploying QoS for IP Next Generation Networks: The Definitive Guide provides network architects and planners with insight into the various aspects that drive QoS deployment for the various network types. It serves as a single source of reference for businesses that plan to deploy a QoS framework for voice, video, mobility and data applications creating a converged infrastructure. It further provides detailed design and implementation details for various service deployments across the various Cisco platforms such as the CRS-1, 12000, 7600 & 7200 series routers that are widely deployed in most Carrier Networks.